Atomistic explanation of brittle failure of thermoelectric skutterudite CoSb3. (15th January 2016) - Li, Guodong; An, Qi; Goddard, William A.; Hanus, Riley; Zhai, Pengcheng; Zhang, Qingjie; Snyder, G. Jeffrey
Abstract: CoSb3 based skutterudite thermoelectric material has superior thermoelectric properties, but the low fracture toughness prevents its widespread commercial application. To determine the origin of its brittle failure, we examined the response of shear deformation in CoSb3 along the most plausible slip system (010)/<100>, using large-scale molecular dynamics simulations. We find that the brittle failure of CoSb3 arises from the formation of shear bands due to the destruction of Sb4-rings and the slippage of Co-octahedraes. This leads to the breakage of Co-octahedraes and cavitation, resulting in the crack opening and mechanical failure. Graphical abstract: